Laboratory exercises in microbiology (John Wiley, 2009)
This book meets the needs of student majoring in diverse programs such as allied health or biological sciences. The manual contains a variety of interactive activities and experiments that teach student the basic concepts of microbiology and support the content covered during lectures.